A proposal to establish indicators for the evaluation of municipal councils’ socio-cultural policies - Planas i Lladó, Anna; Soler i Masó, Pere (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales, 2012)
How can municipal sociocultural policies promote community empowerment, citizenship or social cohesion? What objectives should be proposed at the municipal level to promote processes of sociocultural community development? How can we identify local needs in order to stimulate community development processes? In response to these questions, this paper proposes indicators to evaluate sociocultural policies that will enable us to obtain useful information and, at the same time, contribute to produce changes and possible outlines for strategic interventions. The proposal describes a system of flexible and rigourous indicators intended for municipal technicians and politicians interested in evaluating their sociocultural actions and strategies. We present the result of a research process which included validation by experts and technicians in or related to sociocultural community development, and the application of this system based on a case study of a Spanish municipality. Among the proposed indicators specific consideration is given to the support of local creators and the promotion of civic creativity, as well as the use of sociocultural activities as a strategie to contribute to cultural and civic diversity.